Versatile snail-inspired superamphiphobic coatings with repeatable adhesion and recyclability. (2nd February 2021) - Zhang, Zhenqiang; Yu, Danfeng; Xu, Xiubin; Yang, Hui; Wyman, Ian; Wang, Jinben; Wu, Xu
Graphical abstract: Highlights: Hybrid superamphiphobic coating with repeatable adhesion and recyclability. Snail-inspired versatile and industrially-viable strategy. Hydrogel primer bonds fluorinated nanoparticles finish and substrates. Reduce costs and minimize environmental footprint of superamphiphobic materials. Crude-oil-anti-adhesion, temporary patterned and stretchable superamphiphobicity. Abstract: Superamphiphobic surfaces with extreme repellency toward both water and oily liquids have been developed from various nanocomposites with fluorinated compounds. However, the inherent rigidity and low-surface-energy of these composites restrict their adhesion and practical application in adjusting the surface wettabilities of materials. Here we report a strategy to create hybrid superamphiphobic coating with rapid contact adhesion to various kinds of substrates, strong and controllable adhesive strength, unprecedented capability of mechanical deformations, facile removal, repeatable adhesion, and simple recyclization. Our approach, inspired by snail's ideal combination of hard shell and soft epiphragm, is versatile and industrially-viable because we use the hydrogel primer to bond the fluorinated nanoparticle finish and substrates. Considering the unique characteristics of these coatings as well as the wide range of available hydrogels and nanomaterials that can be used via this approach, we envision that this snail-inspired strategy will facilitate the development and large-scale production of superamphiphobic coatings.